2020
DOI: 10.29271/jcpsp.2020.01.67
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mortality in Fournier's Gangrene with the Two Scoring Systems

Abstract: Fournier's gangrene (FG) is necrotizing fasciitis of the perianal and genital regions, caused by interdependent polymicrobial infections. Identifying the symptoms early is critical as delay in diagnosis and treatment can be fatal. The clinical presentation of this disease is highly variable, ranging from early, localised skin hardening, redness, and swelling to more obvious dermal indications during the later stages including up to sepsis, which is a systemic finding. FG usually begins with perianal or perinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 15 publications
(50 reference statements)
0
11
1
1
Order By: Relevance
“…The FGSI is a good prognostic tool for assessing patients with Fournier gangrene. 4 Mean FGSI in our study was 5.5 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) in the surviving patients (first group), and an average of 14 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) in the deceased patients (second group), which is significantly higher than the first group (p = 0.001). In our study, 11 points was agreed to be taken as the cut-off score rather than 9 as the other study does, but we have still taken the 9-points…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The FGSI is a good prognostic tool for assessing patients with Fournier gangrene. 4 Mean FGSI in our study was 5.5 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) in the surviving patients (first group), and an average of 14 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) in the deceased patients (second group), which is significantly higher than the first group (p = 0.001). In our study, 11 points was agreed to be taken as the cut-off score rather than 9 as the other study does, but we have still taken the 9-points…”
Section: Discussionmentioning
confidence: 50%
“…Hypertension (9.4%), HIV (5.2%), the presence of fistula (6%), stricture (6%), and malignancy (2.3%) were also detected in patients' comorbid history. From the Fournier's Gangrene Severity Index (FGSI), in the first group we found the average score was 5.5 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), and the average was 14 (10-19) in the second group, which is significantly higher than the first group (p = 0.001). In our study with FGSI cut-off score, we found that in the first group, 42 patients (70%) were alive and 1 died (4.3%) with cut-off score < 9, while 49 patients (81.6%) were alive and 4 died (17.3%) with cut off score < 11.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Bei den retrospektiven Untersuchungen handelt es sich um 11 Fallserien mit insgesamt 860 FG Patienten [24][25][26][27][28][29][30][32][33][34][35] sowie eine retrospektive Kohortenanalyse mit epidemiologi-that there is urgent need for therapy improvement. New risk factors for higher mortality in FG have been identified in these studies, namely dyslipoproteinemia, diabetes mellitus, heart disease, as well as both acute and chronic kidney failure.…”
Section: Ergebnisse Aus Den Retrospektiven Studienmentioning
confidence: 99%
“…Dabei kommen die Autoren zu dem Ergebnis, dass die VAC zwar eine effektive Me-BMI = Body Mass Index; FG = Fourniersches Gangrän; FGSI = Fournier´s Gangrene Severity Index; HBO = hyperbare Oxygenierung; HR = Hazard Ratio; KI = Konfidenzintervall; OR = Odds Ratio; UFGSI = Uludag FGSI; VAC = vakuum-assistierter Wundverschluss thode, aber nicht effektiver als eine konventionelle Wundbehandlung ist[39]. hin Optimierungsbedarf gibt[24,29,30,[33][34][35].Radcliffe et al konnten sogar zeigen, dass sich die Mortalitätsrate in den letzten 25 Jahren nicht signifikant geändert hat und bei etwa 19,8 % liegt [33]. Dies stimmt mit den Ergebnissen von Kranz et al aus dem Jahre 2018 überein.…”
unclassified